THE PROTECTIVE SHUTDOWN IN CASE OF THE BREAKAGE OF THE CONTACT WIRES IN THE POWER SUPPLY SYSTEM OF RAILWAY TRANSPORT - Shkrabets, F. P.; Ostapchuk, O. V.; Hrebeniuk, O. M. (Science and Transport Progress, 2008)
The type of damages is considered when the malfunction of regular tools of protection from emergency regimes in a hauling network is probable. The use of device of protecting from the break of a contact wire is offered. The charts of realization of this device under various conditions of hauling networks are presented.